Displacement Characteristics of a Deep Excavation in Hangzhou Soft Clay - Yuan Mei; Lu Wang; Dongbo Zhou; Liaoyuan Fu (Advances in Civil Engineering)
Excavations in a soft soil area are usually associated with substantial difficulties. Taking a special-shaped deep foundation pit in Hangzhou soft clay as the research object, the excavation performances, including groundwater level height, axial force, lateral wall, and soil deflection, and ground surface settlement were monitored and summarized based on the data published in the literature on similar excavations in Hangzhou, P. R. China. The following conclusions are drawn: (1) The axial forces of the struts dynamically change during the excavation and construction or removal of adjacent braces. (2) The ratio between the measured maximum wall deflection and excavation depth δh−max/He is 0.14–0.17%, larger than those in Shanghai. (3) The surface settlement behind the wall has an obvious primary influence zone and secondary influence zone, characterized by a “groove shape” and “triangle shape,” respectively. The maximum ground surface settlement δv−max ranges from 0.29% to 0.5% of the excavation depth. (4) The distribution of the ground settlement was analyzed. The relationship between the maximum settlements δv−max is between 1.28 δh−max and 3.72 δh−max. Moreover, ABAQUS software with Mohr–Coulomb soil models was used for model analysis of the construction process. The research results have important significance for the effective prevention of foundation pit accidents and the optimal design of deep foundation pit projects.